Apoptotic capacity and risk of squamous cell carcinoma of the head and neck. (February 2017) - Liu, Zhensheng; Liu, Hongliang; Han, Peng; Gao, Fengqin; Dahlstrom, Kristina R.; Li, Guojun; Owzar, Kouros; Zevallos, Jose P.; Sturgis, Erich M.; Wei, Qingyi
Abstract: Background: Tobacco smoke and alcohol drinking are the major risk factors for squamous cell carcinoma of the head and neck (SCCHN). Smoking and drinking cause DNA damage leading to apoptosis, and insufficient apoptotic capacity may favour development of cancer because of the dysfunction of removing damaged cells. In the present study, we investigated the association between camptothecin (CPT)-induced apoptotic capacity and risk of SCCHN in a North American population. Methods: In a case–control study of 708 SCCHN patients and 685 matched cancer-free controls, we measured apoptotic capacity in cultured peripheral blood lymphocytes in response to in vitro exposure to CPT by using the flow cytometry–based method. Results: We found that the mean level of apoptotic capacity in the cases (45.9 ± 23.3%) was significantly lower than that in the controls (49.0 ± 23.1%) ( P  = 0.002). When we used the median level of apoptotic capacity in the controls as the cutoff value for calculating adjusted odds ratios, subjects with a reduced apoptotic capacity had an increased risk (adjusted odds ratio = 1.42, 95% confidence interval = 1.13–1.78, P  = 0.002), especially for those who were age ≥57 (1.73, 1.25–2.38, 0.0009), men (1.76, 1.36–2.27, <0.0001) and ever drinkers (1.67, 1.27–2.21, 0.0003), and these variables significantly interacted with apoptotic capacity ( P interaction  = 0.015, 0.005 and 0.009, respectively). A further fitted prediction model suggested that the inclusion of apoptotic capacity significantly improved in the prediction of SCCHN risk. Conclusion: Individuals with a reduced CPT-induced apoptotic capacity may be at an increased risk of developing SCCHN, and apoptotic capacity may be a biomarker for susceptibility to SCCHN. Highlights: We used a flow cytometry method to detect the apoptotic capacity (AC). We examined the AC in 708 head and neck cancer patients and 685 controls. AC was significantly lower in cases than in controls. Decreased AC may be associated with increased risk of head and neck cancer.